Identification of ACOX2 as a shared genetic risk factor for preeclampsia and cardiovascular disease - Johansson, A.; Curran, J.; Johnson, M.; Freed, K.; Fenstad, M.; Bjørge, L.; Eide, I.; Carless, M.; Rainwater, D.; Goring, H.; Austgulen, R.; Moses, Eric; et al. (2011)
Preeclampsia (PE) is a serious complication of pregnancy, which is highly correlated with later life cardiovascular disease (CVD). Many risk factors are common for both diseases, but the contribution of shared genes remains to be determined. In this study, we used an integrative strategy to assess lipid traits as risk factors for PE and CVD by whole genome transcriptional profiling performed on Norwegian decidua basalis tissues (N=95) from preeclamptic and normal pregnancies and on blood lymphocytes (N=1240) from the San Antonio Family Heart Study (SAFHS). Among 222 genes that were differentially expressed (false discovery rate (FDR) P-value <0.05) between the PE, cases and controls, we found one gene, ACOX2 (acyl-coenzyme A oxidase 2, branched chain), that was downregulated in PE whose transcription was also inversely correlated with triglyceride levels (P=5.6 × 10−7; FDR P-value=0.0002) in SAFHS. We further report associations between SNPs in the ACOX2 gene and the transcription level (P-value=0.0045) of the gene, as well as with triglyceride levels (P-value=0.0051). ACOX2 is involved in bile acid production, a process that has been associated with both oxidative stress and regulation of triglyceride levels. Oxidative stress and increased triglyceride levels are known risk factors for CVD and both have also been associated with PE. Our results suggest that downregulation of ACOX2 is a shared risk factor for PE and CVD.